DASAR FILOSOFIS DAN INKLUSIVITAS GUGATAN SEDERHANA DALAM SISTEM PERADILAN PERDATA - Anita Afriana (University Of Bengkulu Law Journal, 2018)
The fast litigation procedure stipulates under the Supreme Court Regulation No. 2 year of 2015. That mechanism only requires small amount of permitted claim, it is 200 million Rupiah in maximum, it also settles claims in a very fast manner, 25 days in maximum. This fast procedural mechanism allocated to settle private dispute is called as “the small claims court”, in which, it is already implemented either in states with the civil law system or the common law system. The research methodology used in this article is juridical-normative and juridical kualitative analyze, to aim the SCC phisophy in Indonesia and the effectivity in enacting this mechanism of small claims court as one of the states that enact the civil judicial system. The results shows that the SCC  in indonesia is an advancement as a means of access to justice, in short it is a simple and inexpensive procedure.  that the fast litigation procedure stipulates under the Supreme Court Regulation No. 2 year of 2015 is effectively enacted in civil judicial system in Indonesia. With society needs nowadays, the effort to increasing good services towards justice seeker, it’s inclusive because of the different mechanism of general judicial system under  HIR/RBG, it is not just about time but also with a judge investigation, simple evidentiary, and without legal effort